Cebor Tradition Local Wisdom Values Opatpuluh in the Dukuh Traditional Village Community as a Social Sciences Learning Resource - Dahlena, Alni; Tetep, Tetep; Nuraeni, Sopi (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2023)
Individuals of Kampung Dukuh have their own uniqueness, which should be visible from their straightforward way of life and submitting to the encompassing standard principles, with this peculiarity turning into a neighborhood insight that can be utilized as a wellspring of social examinations learning, connected with issues that should be visible from the should be visible from the variable of diminishing information on nearby insight. The reason for this study was to get data about the conventional traditions of Kampung Dukuh seen from the presently creating customs like the Cebor Opatpuluh custom. The strategy utilized for this exploration utilizes a subjective contextual investigation technique, which should be visible from the uniqueness of the Dukuh customary town, which has its own qualities. In view of this exploration, the outcomes acquired in villa towns are towns situated in Ciroyom town, Cikelet Locale, Garut Rule, West Java. Dukuh customary town is one of the conventional towns in west Java which actually keeps up with its social practices, including strict qualities, which are areas of strength for exceptionally social standards in light of Islamic regulation. Individuals of Dukuh emphatically trust in the karomah of their precursors and keep up with the standards of their predecessors, including the Cebor Opatpuluh custom that is as yet creating and is as yet feasible today. That custom was made in light of Islamic regulation by the Dukuh people group, it tends to be seen from the time and strage in the execution in view of the standards utilized in Islamic (the strategy for filtration), the qualities contained in the Cebor Opatpuluh twenty first practice of strict qualities, social qualities and social qualities.